COMPARISON OF VISUAL PROSTATE SYMPTOM SCORE WITH INTERNATIONAL PROSTATE SYMPTOM SCORE AND THEIR CORRELATION WITH UROFLOWMETRY IN THE EVALUATION OF MEN WITH BENIGN PROSTATIC ENLARGEMENT (The Research of Medical Science Review, 2025)
OBJECTIVE: To evaluate the association among the visual prostate symptom score, the international prostate symptom score, and uroflowmetry in males diagnosed with benign prostatic enlargement.METHODOLOGY: The current investigation was carried out from April 2024 to December 2024 in the urology department of Jinnah Postgraduate Medical Centre (JPMC), Karachi on 129 patients presenting with symptoms suggestive of benign prostatic hyperplasia (BPH) or lower urinary tract symptoms (LUTS) for longer than two months. This study recruited eligible subjects with the age of 50–80 years to examine the relationship between the international prostate symptom score (IPSS and visual prostate symptom score (VPSS), and uroflowmetric variables in male patients with benign hyperplasia. The resulting dataset was subjected to various statistical analyses using SPSS version 26 that included descriptive proportions and Pearson's correlation coefficientRESULTS: The average age of the participants was determined to be 61.95 years (± 7.33 SD). A robust negative correlation was identified between the International Prostate Symptom Score (IPSS) and the maximum urine flow rate (Q max) (r=-0.831, p=0.000), as well as between IPSS and the average urine flow rate (Q ave) (r=-0.852, p=0.000). Conversely, there was no statistically significant correlation between IPSS and the voided volume (r=0.031, p=0.723). A strong negative correlation was similarly established between the Voiding Perception Symptom Score (VPSS) and the maximum urine flow rate (Q max) (r=-0.830, p=0.000), as well as between VPSS and the average urine flow rate (Q ave) (r=-0.847, p=0.000). However, no significant correlation was detected between VPSS and the voided volume (r=0.004, p=0.962).CONCLUSION: IPSS and VPSS display strong negative correlations with both the maximal and average urine flow rates and, therefore, can be used clinically to assess the severity of symptoms in men with benign prostatic enlargement. Because of its visual format, VPSS is an easily accessible alternative to IPSS, particularly in patients with poor literacy. It is strongly advised that extensive research be conducted in order to substantiate the findings currently presented.